2021
DOI: 10.3390/horticulturae7050100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost Leachate versus Inorganic Fertilizer on Morphology and Microbial Traits in the Early Development Growth Stage in Mint (Mentha spicata L.) And Rosemary (Rosmarinus officinalis L.) Plants under Closed Hydroponic System

Abstract: The objective of this study was to compare the morphology of M. spicata and R. officinalis plants, and the relative abundance quantification, colony-forming units, ribotypes, and biofilm former bacteria under an inorganic fertilizer and the use of vermicompost leachate in the rhizosphere under a closed hydroponic system. In mint (Mentha spicata) plants treated with the vermicompost leachate, growth increase was determined mainly in root length from an average of 38 cm in plants under inorganic fertilizer to 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A study carried out by Loera-Muro et al (2021) [ 53 ] examined the morphology, precisely root length, and microbial traits during the initial growth stage of mint and rosemary plants. The research aimed to cultivate lettuce using vermicompost and thermophilic compost.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Loera-Muro et al (2021) [ 53 ] examined the morphology, precisely root length, and microbial traits during the initial growth stage of mint and rosemary plants. The research aimed to cultivate lettuce using vermicompost and thermophilic compost.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Loera-Muro et al [7] recommended using vermicompost leachate fertiliser as a feasible replacement for inorganic fertiliser in hydroponic systems to achieve sustainable and eco-friendly agricultural production. The use of vermicompost leachate allows the maintenance of rosemary (Rosmarinus officinalis L.) or the increase in the production of mint (Mentha spicata L.) and with neither the modification of the bacterial communities for both plants nor changes to their ability to form biofilms.…”
Section: Special Issue Overview and A Short Discussionmentioning
confidence: 99%
“…Certification to the USDA organic standards is currently allowed if it is certifying to comply with the NOSB recommendations. However, which hydroponic practices align or do not align with the Organic Foods Production Act and USDA organic regulations is the subject of intense debate [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, fertilization with a combination of 25% urea (23,75kg N ha -1 ) and 75% vermicompost (10,1t ha -1 ) significantly increased the number of leaves and the yield of essential oils in M. arvensis and M. piperitha (Keshavarz et al, 2018). Loera-Muro et al (2021) proposed the substitution of inorganic fertilizers by vermicompost leachates in hydroponic crops of Mentha spicata and Rosmarinus officinalis. Their study demonstrated that such organic fertilizer doubled root biomass production in both species.…”
Section: Discussionmentioning
confidence: 99%